Literature Review Isu-Isu Kontemporer Manajemen Pendidikan Islam: Antara Transformasi, Etika, dan Inovasi - Rahayu Lestari; Nur Fahmuddin Hanif; Shera Nabila luvianingtias; Tin Amalia Fitri; Amiruddin (At Turots: Jurnal Pendidikan Islam, 2025)
This study presents a comprehensive literature review on contemporary issues in Islamic Education Management (IEM), emphasizing three interconnected dimensions: institutional transformation, ethics-based governance, and innovation in management and learning. Using an analytical-descriptive approach, the review synthesizes findings from national and international journals published within the last five years to identify emerging challenges and strategic responses in modern IEM practices. The results indicate that institutional transformation provides a structural foundation for adaptive change, while ethics and Islamic value-based governance ensure that managerial decisions remain aligned with moral and spiritual principles. Innovation serves as a catalyst that enhances educational quality through digital integration, human resource development, and curriculum renewal. These three elements are interrelated and mutually reinforcing, forming a holistic framework that balances modernization with Islamic ethical identity. The study concludes that effective Islamic education management must harmonize transformative strategies, ethical integrity, and sustainable innovation to achieve relevance, competitiveness, and spiritual authenticity in the contemporary era.